0.5
4=3x-14 18=3x I carried the 14 over and it became positive. x=6 I divided 18 by 3.
6-3x+12=0 6+12-3x=0 18-3x=0 18=3x x=6
3x-3 = 6 3x = 6+3 3x = 9 x = 3
0.4286
6x-3x =6 3x=6 so 6 divided by 3 = 2
(x - 3x - 6) / 6 = (3x + 2) / 3 ∴3x - 9x - 18 = 18x + 12 ∴3x - 9x - 18x = 12 - 18 ∴-24x = -6 ∴ x = 1/4
(x - 3x - 6) / 6 = (3x + 2) / 2 ∴2(3x + 2) = 6(3x + 2) ∴6x + 4 = 18x = 12 ∴12x = -8 ∴x = -2/3
0.5
If 2 divided by 3x it is equal to 2/3x
3 / 9x+63 / 3(3x+2)1 / 3x+2
x = 1 1/2 = [14 dividedby (6x - 2) ] - [6 dividedby (3x - 1) ]
4=3x-14 18=3x I carried the 14 over and it became positive. x=6 I divided 18 by 3.
y = mx + b (where m is the slope) So -3x - 5y = 6 (add 3x to both sides) -5y = 3x + 6 (divided both sides by -5) y = -3/5x - 6/5 Slope is -3/5 or -.6
9x2 + 3x / 3x equals (3x + 1).9x2 + 3x divided by x is 9x + 3 , and then divided by 3 yields the 3x +1.
9
That depends entirely on the value of x.